Intestinal parasitism and competency achievement in students of the Margarita Santa Ana de Benavides educational institution, Ica, Peru - Donayre-García, Danne Douglas (2024)
The high incidence of intestinal parasites compromises health and academic performance in regions with inadequate sanitation. The objective of this study was to describe the relationship between intestinal parasitosis and the achievement of competencies among students at the Margarita Santa Ana de Benavides educational institution in Ica, Peru. This quantitative, basic, non-experimental study employed a correlational design to evaluate 80 conveniently selected secondary school students. Three fecal samples were collected per student, and a questionnaire was administered to measure communication competencies. The statistical analysis included the Kolmogorov-Smirnov test for normality and Chi-square (X²) analysis to assess the relationship between parasitosis and competencies. Of the 80 students evaluated, 27 (33.8%) exhibited parasitosis, while 53 (66.2%) did not. Regarding communication competencies, 5% of the parasitized students achieved them compared to 25% of the non-parasitized students. The analysis revealed a significant relationship between parasitosis and competency achievement, indicating that parasitosis negatively affects academic performance in communication. These results underscore the necessity of implementing public health interventions in vulnerable school contexts to improve both the physical well-being and academic performance of affected students.